Solid waste management in construction site and effect to environment (water pollution) / Mohd Khairi Kurdi - Kurdi, Mohd Khairi (2008)
Nowadays many pollution problems caused by irresponsible parties are reported. The community has felt the pinch of environmental impacts in daily life as these problems such as lack of supervision in term of solid waste management affect the environmental safety and the quality of life. Insufficient collection and inappropriate disposal of solid wastes give rise to land, water and air pollution, and pose risks to human health and environment Solid waste management encompasses the planning, design, financing, construction and operation of facilities for collecting, transporting, processing, recycling and final disposal of the residual solid material. Solid waste is any matter prescribed to be scheduled waste, or any matter whether in a solid, semi-solid or liquid form, or in the form of gas or vapor which is emitted, discharged or deposited in the environment in such volume, composition or manner so as to cause pollution to the environment. The Pollution is any direct or indirect alteration of the physical properties so as To affect any beneficial use (of any part of the environment) adversely, To cause a condition this is hazardous or potentially hazardous to public health, safety, or welfare, or to animals, birds, wildlife, fish or aquatic life, or to plants. Other affect is to cause a contravention of any condition, limitation or restrictions to which a license under this Act is subject.